Insidince of Viral Infection and Relationship with Cat Husbandry Practices after Covid-19 Pandemi in Citrapet and Vet - Siagian, Tetty Barunawati; Alghiffari, Rizieq (Program Studi Peternakan, Fakultas Pertanian, Sains dan Kesehatan, Universitas Timor, 2025)
The trend that occurred during the pandemic persisted after the Covid-19 pandemic where many people kept cats. The cat population has increased after the pandemic. Cat owners have returned to their previous activities and this condition affects their cat care practices after the pandemi. Purpose of this study was to describe the correlation between the incidence of viral infections and cat husbandry practices after the Covid-19 pandemi. This study used medical records of cat patients who came to Citrapet and Vet with viral diagnoses and 100 cat owner respondents using structured questionnaires. Cases of viral infections that occurred at Citrapet and Vet were included in the small category of 179 cases with a percentage of 0.033%. The cause of this small category of viral infection cases is the cat maintenance practices carried out by cat owners in Citrapet and vet. Parameters that are the reference include; vaccination, maintenance methods, administration of antiparasitic drugs, and medical checkup. Results of the respondents show that almost all cat owners in Citrapet and Vet understand how to perform cat maintenance practices properly and correctly. One of the parameters as a reference, namely vaccination, showed results with 88% of cats coming to Citrapet and Vet being vaccinated. This shows that vaccination can reduce the incidence of viral infections. Statistical calculations showed a significant correlation between cat husbandry practices and the incidence of viral infections in post-pandemi pet cats.